Implication of Oxidative Stress, Aging, and Inflammatory Processes in Neurodegenerative Diseases: Growth Factors as Therapeutic Approach - Herrera, Macarena Lorena (2019)
Oxidative stress (OS) is defined as the imbalance between the production of reactive oxygen species (ROS) and the antioxidant defense system. Living organisms produce ROS from molecular oxygen as a consequence of normal cellular metabolism. In order to prevent damage, cells have an antioxidant defense system constituted by an enzymatic component (including catalases, superoxide dismutases, etc.) and nonenzymatic antioxidants component (glutathione, α-tocopherol, ascorbic acid, etc.). When the levels of ROS exceed cell capacity, it can cause damage in cellular components such as carbohydrates, nucleic acids, lipids, and proteins, thus altering their function. Whenever this imbalance occurs within the central nervous system, it can lead to the development of the neurodegenerative disorders. Neurodegenerative diseases are characterized by the loss of neuronal cells and, in most cases, by the aggregates of proteins that form intracytoplasmic and intranuclear inclusions in neurons and glial cells. Data on the literature show that there are two possible mechanisms involved in most of neurodegenerative diseases: (1) mutations and/or aggregation of characteristic proteins of each disease such as α-synuclein in Parkinson’s disease (PD) or beta-amyloid peptide in Alzheimer’s disease (AD) and (2) dysfunction of mitochondrial energy metabolism in neurons. In this section, we will focus on this last one.